2020
DOI: 10.1101/2020.12.19.20248508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Several forms of SARS-CoV-2 RNA can be detected in wastewaters : implication for wastewater-based epidemiology and risk assessment

Abstract: The ongoing global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a public health emergency of international concern. Although SARS-CoV-2 is considered to be mainly transmitted by inhalation of contaminated droplets and aerosols, SARS-CoV-2 is also detected in human feces and in raw wastewaters suggesting that other routes of infection may exist. Monitoring SARS-CoV-2 genomes in wastewaters has been proposed as a complementary app… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 58 publications
(76 reference statements)
2
19
1
Order By: Relevance
“…In this study, 18S rRNA signal displayed a wide range in concentrations and consistently amplified in negative extraction controls. Furthermore, 18S rRNA was less stable in wastewater than SARS-CoV-2 RNA and nonenveloped viruses (e.g., crAssphage and PMMoV), which is consistent with previous studies ( Whitney et al, 2021 ; Wurtzer et al, 2020 ). Therefore, we do not recommend 18S rRNA use as a normalization biomarker.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, 18S rRNA signal displayed a wide range in concentrations and consistently amplified in negative extraction controls. Furthermore, 18S rRNA was less stable in wastewater than SARS-CoV-2 RNA and nonenveloped viruses (e.g., crAssphage and PMMoV), which is consistent with previous studies ( Whitney et al, 2021 ; Wurtzer et al, 2020 ). Therefore, we do not recommend 18S rRNA use as a normalization biomarker.…”
Section: Discussionsupporting
confidence: 92%
“…San Quentin Prison (location Q) had a COVID-19 outbreak during the study period after a transfer from the California Institution for Men ( Cassidy and Fagone, 2020 ), where, at its peak, 47% of the incarcerated population had active COVID-19 cases. The maximum SARS-CoV-2 N1 concentration (4.89 × 10 3 gene copies/mL) was higher than any sewershed sampled in this study and among the highest values we found in the literature for N1 in raw wastewater ( Gerrity et al, 2021 ; Gonzalez et al, 2020 ; Medema et al, 2020 ; Randazzo et al, 2020b ; Wu et al, 2020 ; Wurtzer et al, 2020 ), despite regular clinical testing ( Figure S15 ). Prison conditions cause incarcerated people to be particularly susceptible to respiratory disease outbreaks, and maintaining safety in prisons requires deliberate planning and coordination by correctional institutions (e.g., coordination with local public health systems to develop pandemic response plans, coordination of transfers between institutions, etc.)…”
Section: Discussionmentioning
confidence: 46%
“…San Quentin Prison (location Q) had a COVID-19 outbreak during the study period after a transfer from the California Institution for Men (Cassidy and Fagone, 2020), where, at its peak, 47% of the population had active cases. The maximum SARS-CoV-2 N1 concentration (4.89 x 10 3 gene copies/mL) was higher than any sewershed sampled in this study and among the highest values we found in the literature for N1 in raw wastewater (Gerrity et al, 2021;Gonzalez et al, 2020;Medema et al, 2020;Randazzo et al, 2020b;Wu et al, 2020;Wurtzer et al, 2020), despite regular clinical testing (Figure S15). Prison conditions cause incarcerated people to be particularly susceptible to respiratory disease outbreaks, and maintaining safety in prisons requires deliberate planning and coordination by correctional institutions (e.g., coordination with local public health systems to develop pandemic response plans, coordination of transfers between institutions, etc.)…”
Section: Validation and Potential Use Scenarios Of Sars-cov-2 Wastewater Testingcontrasting
confidence: 47%
“…At the same time, there has been increased management, measurement and monitoring of wastewater quality related to viral presence [40,41]. This is because in wastewater could result in high concentrations of viral RNA in the receiving water bodies if the wastewater is not adequately treated [42]. Hence, to help contribute to the monitoring of the virus across the globe, academic and governmental communities (mainly in developed countries) have initiated strategies that seek to report and quantify the presence of the virus in wastewater and surface water sources.…”
Section: Wastewater and Sars-cov-2mentioning
confidence: 99%